Le leggi della formazione del mito nel pensiero di E. Burnett Tylor - Ciattini, Alessandra (EtnoAntropologia, 2018)
The aim of this article is to reinterpret Tylor’s reflection on myth, avoiding what Stocking defines as a presentist approach. I will try to contextualize the vision of the Victorian Author firstly by saying that he was neither a direct descendent of Darwin nor even an evolutionist. Secondly, I will try to demonstrate that the continuist perspective of the relationship between myth and science, reproposed by the neo-intellectualists, can be accepted even today, provided we also emphasize the differences between the two phenomena: differences which, in substance, amount to the absence of a self-critical attitude in the builder of myths. Were such attitude present, after all, myths would not exist.